EFEKTIVITAS RUMBLE STRIPS DALAM MEREDUKSI KECEPATAN ARUS LALU LINTAS DI JALAN LINGKUNGAN UNIVERSITAS RIAU - Benny Hamdi Rhoma Putra; Edi Yusuf Adiman; M. Rilly A Yogi; Choryn Munadiyatul Haq; Elianora Elianora (Racic : Rab Construction Research, 2023)
University of Riau (UNRI) Binawidya Campus, has approximately 700 hectares area which consist of 10 faculties. With good pavement conditions and the distance between faculties that are far apart, the characteristics of the speed of vehicles along UNRI Environmental Roads are high. High vehicle speed causes traffic safety problems, infact, increasing the probability of traffic accidents. One of the traffic engineering that has been applied to the UNRI Environmental Road is the installation of Rumble strips at many points on the campus Environment Road. The initial goal with the installation of this noise tape is to reduce vehicle operational speed (traffic calming) and reduce the possibility of accidents. This study aims to analyze the effectiveness of rumble strips in reducing the speed of traffic flow on the environmental roads of the University of Riau, namely on Muchtar Lutfi Street, the road next to the Rectorate Mosque, and the road in front of Faperta. The method of data collection is through a survey of the average speed of motorcycles (MC) and light vehicles (LV). Comparative analysis of the decrease in vehicle speed when passing through rumble strips using the chi-square test. The results of the chi-square test showed that there was no significant change in the average speed of vehicles affected by rumble strips to reach the vehicle speed limit of 40 km/hour at the University of Riau. This phenomenon arises because the design of the rumblestrips is not in accordance with the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 82 of 2018 both in terms of number and dimensions. Recommendations that can be applied are to adjust to the design of the provisions, and complement the rublestrips with caution signs and emblems.